Robotic vs laparoscopic splenectomy for splenomegaly: A retrospective comparative cohort study. (July 2018) - Cavaliere, Davide; Solaini, Leonardo; Di Pietrantonio, Daniela; D'Acapito, Fabrizio; Tauceri, Francesca; Framarini, Massimo; Ercolani, Giorgio
Abstract: Background: The aim of this study was to evaluate the role of robotic total splenectomy for splenomegaly, comparing this approach with the laparoscopic technique. Methods: We conducted a retrospective review of all patients who underwent minimally invasive splenectomy for splenomegaly (maximum splenic diameter>15 cm) at our institution between 2000 and 2017. Results: A total of 39 patients (27 laparoscopic vs 12 robotic splenectomies) were included in the study. Operative time was significantly longer in the robotic group (270 min vs 180 min, p = 0.007). Median intraoperative blood loss was 350 ml for laparoscopic procedures while it was 100 ml for the robotic ones (p = 0.032). Conversion to open surgery was required in 4 cases of laparoscopic splenectomy while no conversion were registered in the robotic group. No significant differences were seen in postoperative morbidity and mortality between the two groups. Conclusions: Robotic splenectomy for splenomegaly is associated with less blood loss and longer operative times than the laparoscopic procedure. Highlights: Laparoscopic splenectomy is the gold standard for spleen of normal size. Laparoscopic splenectomy is challenging in case of splenomegaly. Robotic splenectomy is feasible and safe. Robotic splenectomy is associated with better outcomes than laparoscopy.